Trade, services and development : the regulatory and institutional challenges (UN New YorkUS, 2013)
Focuses on some key regulatory and institutional challenges in infrastructure services sectors (ISS) as these play an enabling role in improving productivity and building the supply capacity of services in a country.
Keywords: SERVICE INDUSTRY